Grammatical Cohesions in Inaugural Speeches of Barrack Obama and Donald Trump - Good Sumbayak Lingga; Nurlela Majrul; Alemina Br Perangin-angin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
The purpose of this thesis is to look at the different forms of grammatical cohesions and why they were used in Barack Obama's and Donald Trump's inaugural addresses. This thesis employs a descriptive qualitative technique to describe the study's issues in Barrack Obama's and Donald Trump's inaugural addresses. Based on Halliday and Hasan's theory, the data are collected using library research techniques and grouped into the categories of grammatical cohesions as well as the reasons for employing them. After examining both Barrack Obama's and Donald Trump's inaugural speeches, it can be determined that Barrack Obama's inaugural speech has three types of grammatical cohesions while Donald Trump's inaugural speech has four types of grammatical cohesions. In both speeches, such categories are used to connect two things' meanings, to replace one item with another, to delete an item, and to relate the previous or following material.